The distance between the religious values of parents and those of children in Israel - Luria, Ela (Frontiers in Psychology, 2024)
Prior research into the socialization of religious values between religious parents and their children indicates that, in homogeneous religious family groups, there are similarities between the religious values of religious parents and those of their children. Research further shows that, in religious-secular heterogeneous family groups, there is a significant distance between the religious parent and their teenagers in terms of religious values. The purpose of this study is to explore the transmission of religious values in homogeneous Modern-Orthodox family groups and in heterogeneous Modern-Orthodox-secular family groups in Israel. Results of the study show that religious distance in values is not dependent on the family type (homogeneous/heterogeneous). However, it appears that, when the transmitter of religious values is a religious parent in both homogeneous and heterogeneous religious and religious-secular family groups, there is a distance in the socialization of religious values between religious parent and their children. Moreover, the study proposes that the effect sizes are smaller in the parent-child religious distance of values in homogeneous Modern-Orthodox family groups in comparison to the parent child religious distance of values in heterogeneous Modern-Orthodox-secular family groups. This study provides support for recent research, suggesting that the transmission of religiosity from parents to their children might function as a mechanism of secularization.